"دور التسويق الرقمي في تعزيز التمكين الاستثماري للقطاع السياحي دراسة حالة: وكالة بن علي للسياحة والأسفار – الوادي" - العيد, مقدود; عبد اللطيف, تامه (unuversity of eloued- جامعة الوادي, 2023)
هدفت هذه الدراسة إلى توضيح أهمية التسويق الرقمي كآلية لتعزيز التمكين الاستثمار السياحي، لقد تم تقديم إطار نظري يحدد ويعرف مختلف المفاهيم المتعلقة بالتسويق الرقمي الاستثمار السياحي والذي اعتمد فيه على المنهج الوصفي،حيث تم التأكيد استخدام تقنيات التسويق الرقمي مثل محركات البحث والإعلانات على وسائل التواصل الاجتماعي والتسويق بالبريد الإلكتروني . أما الجانب التطبيقي فاستعمل المنهج الإحصائي باستخدام برنامج APSS وقد حاولنا الوقوف على أراء إطارات الوكالة محل الدراسة وتحليلها. وقد خلصت الدراسة إلى وجود علاقة ذات دلالة إحصائية بين التسويق الرقمي -ببعده الأول تسويق الخدمات عبر الانترنيت وببعده الثاني المزيج التسويقي الرقمي- و بين التمكين الاستثماري للقطاع السياحي.وأوصت الدراسة بالاعتماد على التسويق الرقمي من خلال تمكين الاستثمار للشركات السياحية واستخدام التحليلات الرقمية لتحليل سلوك العملاء وتحديد الاحتياجات والاهتمامات الخاصة بهم وتحديد أفضل استراتيجيات التسويق This study aims to elucidate the significance of digital marketing in enhancing the empowerment of tourist investments. A theoretical framework was presented to precisely define and identify various concepts pertaining to digital marketing and tourist investment, utilizing a descriptive methodology. The study underscored the utilization of digital marketing techniques such as search engines, social media advertising, and email marketing. On the practical front, the statistical method was employed with the utilization of the SPSS Program to comprehend and analyze the perspectives of the agency executives under investigation. The study ascertained a notable correlation between digital marketing, specifically internet service marketing as the primary dimension, and digital marketing mix as the secondary dimension, with the empowerment of investment in the tourism sector. Consequently, the study recommends the reliance on digital marketing to enable investment for tourism companies, as well as the utilization of digital analytics to analyze customer behavior, discern their requirements and interests, and determine the most effective marketing strategies
Keywords: التسويق الرقمي،المزيج التسويقي الرقمي، التمكين الاستثماري، القطاع السياحي، وكالة سياحية بالوادي.; digital marketing, digital marketing mix, investment empowerment, tourism sector, tourist agency in El-Oued..